2020
DOI: 10.1021/acsanm.0c01536
|View full text |Cite
|
Sign up to set email alerts
|

Omnidirectionally Stretchable Metal Films with Preformed Radial Nanocracks for Soft Electronics

Abstract: Flexible and stretchable conductive thin films are required for the development of soft electronics; however, few existing films satisfy the requirements for both electrical/ mechanical performances and process practicability. This study describes a simple approach to fabricate omnidirectionally and highly stretchable nanocracked metal thin films on thiolated elastomeric substrates by exploiting the eruption of a residual solvent contained in an elastomeric substrate during metal thermal evaporation. Also, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…It mimics some of the biological skin senses and provides a promising sensing platform for key application areas such as wearable sensors, robotics, and prosthetics (Figure 1). [1,[4][5][6][7][8][9][10][11] However, serious concerns have arisen regarding the production of electronic waste (e-waste), the influence of e-skin on human health, the safety of wearable electronic devices, costs, and environmental limitations. These concerns have encouraged researchers to develop biocompatible, renewable, sustainable, and biodegradable flexible wearable detection devices and biosensing platforms.…”
mentioning
confidence: 99%
“…It mimics some of the biological skin senses and provides a promising sensing platform for key application areas such as wearable sensors, robotics, and prosthetics (Figure 1). [1,[4][5][6][7][8][9][10][11] However, serious concerns have arisen regarding the production of electronic waste (e-waste), the influence of e-skin on human health, the safety of wearable electronic devices, costs, and environmental limitations. These concerns have encouraged researchers to develop biocompatible, renewable, sustainable, and biodegradable flexible wearable detection devices and biosensing platforms.…”
mentioning
confidence: 99%
“…The formation of surface wrinkles in the conductive layers of the substrates enhances the contact interface, surface area, and current pathways, which significantly improve the sensing response and performance. [3,4,95] The ultrasensitive flexible sensors and transparent electrodes, comprising a conducting material and a soft substrate, are essential components for the fabrication of e-skins, photoelectronics, POC diagnostics platforms, and implantable electronics. In this section, we will discuss the application of engineered wrinkle formations in the development of various types of sensors, such as strain, pressure, temperature, photonic, and chemical sensors.…”
Section: Applications Of Surface Wrinkling In Flexible and Stretchabl...mentioning
confidence: 99%
“…have demonstrated that the dependence of thin film surface geometry obtained from gold evaporation on elastomeric thiolated support. [ 181 ] They showed that radially nanocracked films present a higher stretchability than uncracked films, because the propagation of cracks is retarded in the stretching direction.…”
Section: Materials For Intrinsically Stretchable Organic Solar Cellmentioning
confidence: 99%